La red de apoyo social de personas mayores: características estructurales y funcionales según dispositivo de apoyo formal - J. Arias, Claudia (2023)
Social support is highly relevant in old age, contributing to the biopsychosocial well-being. There is extensive evidence regarding the relationship of social support with global well-being and the achievement of a competent old age. However, its availability varies throughout the life course. The network goes through quantitative changes –losses and additions of relations- and qualitative ones –intensification or weakening of the link-. In elderly it tends to decrease in size and even more so in advanced ages. It should be noted that, in the face of these transformations, it is expected that the increase in the need for care will occur together with the decrease in available social support resources. Indeed, elderly people are the most likely to have little support from family and friends. It is even probable that they have lost most of the members that made up their network of relationships and that they have even outlived their own children. This article presents the results of a quantitative research in which the social support networks of older people who attend formal support organizations were explored: educational workshops, day centers, day clubs and long-term residences.  The structured interview of sources of social support was administered to 160 people between 75 and 90 years of age. The results show differences in favor of those who attend the day club in terms of network size, number of family ties and those who provide practical help and companionship. It is concluded that the organizations explored constitute socialization spaces that, in addition to providing formal support, contribute to establishing new links that strengthen informal support networks.